FACTORS OF AFFECTING CHANGES IN PISAU SURIT DANCE STYLE: AN ANALYSIS IN PERSPECTIVE OF ADAPTION THEORY BY ROY A RAPPAPORT - BIJAK GINTING (CV KULTURA DIGITAL MEDIA, 2020)
This study attempts to describe the factors that influence changes in the Pisau Surit dance style. In this discussion, Roy A Rappaport's adaptation theory is used. This research is a literature study conducted with secondary data. Secondary data is extracted from books, journals, and other sources that are compatible with the research theme. The results of the study show that changes in dance style are influenced by sociological factors where social changes also contribute to changes in dance styles. This social change encourages people to be less concerned with the dance tradition. This will also one day turn into popular culture with changes in style that are adapted according to contemporary aesthetic needs.